Penggunaan Situs Liveworksheets untuk Mengembangkan LKPD Interaktif di Sekolah Dasar - Asri Fauzi; Aisa Nikmah Rahmatih; Dyah Indraswati; Muhammad Sobri (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
Interactive student worksheets are a very important part of learning media to support the learning process to achieve the expected goals. The use of the liveworksheets site is one way to develop interactive worksheets so that online learning can run well. The purpose of this community service is to provide knowledge to teachers to take advantage of the free liveworksheets site to develop interactive worksheets so that the obstacles to teaching and learning activities during the Covid-19 pandemic can be overcome. The method of implementing this service begins with observations to partner schools before the implementation of training activities to discuss the time and need for facilities and infrastructure. Then during the training, the activity begins with the provision of material related to interactive student worksheets and how to create interactive student worksheets using the live worksheet site. Furthermore, assistance is provided during practice for teachers or training participants. The results of this service can be said to be successful, as seen from the enthusiasm of the teacher listening to the material and the practice of making interactive worksheets questions. The types of questions that were successfully practiced by the participants were the types of multiple-choice questions, short entries, descriptions, join arrows, dropdowns, drag and drop, checkboxes, word search, and listening and speaking questions. Therefore, with the increasing ability of teachers to create interactive worksheets, it is hoped that teachers can develop more perfect interactive worksheets that are made according to the needs of students. In addition, the knowledge that has been obtained from this training is expected for teachers to share their knowledge and knowledge with other teachers.